Optimizing Critical Care for the Obese Population: From Physiology to Practice - Argoseto Argoseto; Bowo Adiyanto; Erlangga Prasamya (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2026)
Obesity poses distinct issues in the Intensive Care Unit (ICU) owing to its related physiological changes, comorbidities, and the intricacies of management. Obese individuals face heightened risks for respiratory problems, cardiovascular issues, and metabolic dysregulation.Effective management necessitates customized strategies: Respiratory Support: Elevated positive end-expiratory pressure (PEEP), prone positioning, as well as tailored ventilatory modifications are crucial for managing impaired breathing mechanics and averting lung injury. Hemodynamic Management: Careful fluid management and non-invasive monitoring are needed to address altered cardiovascular dynamics and optimize perfusion. Pharmacologic Adjustments: Dosage modifications for sedatives, analgesics, and vasoactive agents accommodate altered drug metabolism and distribution. Nutritional Support: Hypocaloric, high-protein feeding is advised to meet energy needs while avoiding overfeeding, ideally guided by indirect calorimetry. Thromboprophylaxis and Mobility: Heightened risk for venous thromboembolism (VTE) requires higher anticoagulant doses and early mobilization using bariatric equipment. Furthermore, obesity can also caused obesity paradox, an unexpected survival benefit in septic patients with obesity, likely due to enhanced energy reserves, RAAS activation, and anti-inflammatory effects.A multidisciplinary and individualized approach is critical to improving outcomes in obese ICU patients, highlighting the need for updated clinical guidelines and further research tailored to this population.